2014
DOI: 10.4314/ejhs.v24i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Attack on Membrane Lipid and Antioxidant Vitamins in the Course of Pre-Eclamptic Pregnancy

Abstract: BackgroundDespite the volume of knowledge and daily reports on pre-eclampsia, its pathogenesis is still yet to be ascertained. Oxidative stress (oxidant (free radical) in excess of antioxidant) injury is one of the recently suggested pathogenetic mechanisms. This study, however, was designed to determine second and third trimesters of plasma malondialdehyde (product of free radical attack on membrane lipid) and vitamins C and E in pre-eclamptic Nigerian women.Subjects and MethodsA Total of 100 subjects, each f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Free radicals and other damaging reactive oxygen species can cause lipid peroxidation by oxidative metabolic processes then their activation is thought to increase during pre-eclampsia .In the course of the reaction of free radical with polyunsaturated membrane lipid, a systemic stable product malondialdehyde is produced and this is currently being used as an index of free radical injury . In our study, we observed an increase in plasma malondialdehyde level in preeclamptic women when compared with normal pregnant our findings is in agreement with similar studies which reported a significantly elevated level of malondialdehyde in both normal and preeclamptic pregnant women [17,18]. Endothelial cell dysfunction in glomerula leads to reduction in renal perfusion and glomerular filtration in pre eclampsia.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Free radicals and other damaging reactive oxygen species can cause lipid peroxidation by oxidative metabolic processes then their activation is thought to increase during pre-eclampsia .In the course of the reaction of free radical with polyunsaturated membrane lipid, a systemic stable product malondialdehyde is produced and this is currently being used as an index of free radical injury . In our study, we observed an increase in plasma malondialdehyde level in preeclamptic women when compared with normal pregnant our findings is in agreement with similar studies which reported a significantly elevated level of malondialdehyde in both normal and preeclamptic pregnant women [17,18]. Endothelial cell dysfunction in glomerula leads to reduction in renal perfusion and glomerular filtration in pre eclampsia.…”
Section: Resultssupporting
confidence: 92%
“…Increase in oxidative stress markers has been implicated to damage the maternal vascular endothelium leading to the elevation in diastolic pressure which further aggravates the condition of preeclamptic patients [18,19]. The imbalance between oxidative damage and antioxidant defences in pre-eclampsia leads to endothelial cell dysfunction and it appears to be a central feature in the patho-physiology of preeclampsia [17]. Compared with healthy pregnant women, preeclamptic women have low levels of several dietary antioxidants in their blood, including vitamin C, vitamin E, and lycopene and beta carotene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be justified as the vitamin is a reducing agent, and is considered as a “preventative” or “primary” antioxidant because it acts as a first-line defense mechanism for the plasma and cytosol. It reacts with free radicals such as superoxide and hydrogen peroxide, by donating electrons to destroy them before they react with lipoproteins and membranes, avoiding lipid peroxidation and the beginning of the oxidative process [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that 80% DMSO did not result in a halo, indicating that 80% DMSO was not toxic in yeast cells ( Figure S11 ). Membrane proteins are often targets of free radical attacks, which lead to lipid peroxidation, cell leakage and death [ 52 , 53 ]. We analyzed intracellular oxidation and lipid peroxidation in cells treated with herbal teas and green teas extracts to test whether these herbal teas and green teas can protect against the oxidative damage.…”
Section: Discussionmentioning
confidence: 99%